Phospholipid methylation in starfish spermatozoa is linked to sperm chemoattraction. - Tezon, J (1986)
The mechanism whereby ovarian peptides cause sperm attraction was studied in the starfish. Phospholipid methylation and protein-O-carboxyl methylation, reactions linked to chemotactic responses in a variety of systems, were studied in starfish sperm. When sperm were preincubated with [methyl-3H]methionine and then exposed to the attractant, a rapid drop in radioactivity occurred in the phospholipid fraction. Methylated phospholipids decreased by 90% in the first 2 sec; however, no change was observed in endogenous methylation of protein carboxyl groups. The effect on phospholipid methylation was dose dependent, with a 40% reduction in radioactive phospholipids in sperm occurring with the minimal amount of attractant necessary to obtain a positive response in a sperm attraction bioassay. Attractants from species of starfish with little or no cross-reactivity in the bioassay had a limited effect on phospholipid methylation. The transmethylase inhibitor, homocysteine, caused a marked decrease in the accumulation of methylated phospholipids under basal conditions, which was correlated with as much as a 50-fold increase in sperm sensitivity to the attractant. The addition of chemoattractant resulted in a reduction in the amount of all individual methylated phospholipids, but the amount of phosphatidylmono[3H]methylethanolamine relative to the other methylated phospholipid decreased by a factor of 4 after stimulation. Homocysteine had the same effect. The reduction in methylated phospholipids by attractants suggests that phospholipid methylation is linked to the mechanism of action of these peptides. Methylation of phospholipids may play a role in the rapid desensitization of sperm cells to the attractant, which would be required for the orientation of the spermatozoa in the gradient of ovarian peptide.